Der Süden und der Norden als Paradigmen des Kunstschaffens am Beispiel von Hans E. Kincks Novelle „Renaessance“ - Brynhildsvoll, Knut (Folia Scandinavica Posnaniensia, 2007)
In my contribution I aim at giving a close reading of Hans E. Kinck’s novel “Renxssanse” focusing on two different aesthetic approaches to artistic creativity and craftsmanship, one of which is linked to Nordic romanticism and the other one to the epigonal forms of southern (Italian) Renaissance art, each of them with separate referential outlooks to Friedrich Schiller’s conceptions of naive vs. sentimental notions of literary representation. The nalysis shows how the main figure pays for his success as a master of superficial pseudo-renaissance art with the loss of his original talent and his decline as an artist that finally leads to his madness and death.